1985
DOI: 10.1128/jcm.22.4.576-581.1985
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic Escherichia coli in a population of infants with diarrhea in Chile

Abstract: The incidence of enterotoxigenic Escherichia coli (ETEC) was investigated in 95 E. coli strains isolated from 48 infants with diarrhea in Santiago, Chile. By using standard biological assays and DNA-DNA hybridization procedures, ETEC was found in 31.2% of the cases: 14 strains produced heat-stable enterotoxin (ST) only, three strains produced heat-labile enterotoxin (LT) and ST, and two strains produced LT only. DNA probes detected all enterotoxin producers except one ST-producing strain. The ST strains hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 45 publications
(55 reference statements)
1
6
0
1
Order By: Relevance
“…Outer membrane proteins were extracted and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (1,11). Colony DNA hybridization and Southern hybridization of restriction enzyme-digested chromosomal DNA were performed as previously described (2,11,12). The DNA probe for the 36-kDa porin gene was an intragenic PvuII-PstI DNA fragment of 800 base pairs from plasmid pST13 (1).…”
Section: Methodsmentioning
confidence: 99%
“…Outer membrane proteins were extracted and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (1,11). Colony DNA hybridization and Southern hybridization of restriction enzyme-digested chromosomal DNA were performed as previously described (2,11,12). The DNA probe for the 36-kDa porin gene was an intragenic PvuII-PstI DNA fragment of 800 base pairs from plasmid pST13 (1).…”
Section: Methodsmentioning
confidence: 99%
“…An initial study found that 86 % of ETEC isolated from students becoming ill when visiting Mexico produced CFA/I [21] but when a collection of ETEC from several countries and of different serotypes were tested a much lower proportion of strains were found to produce this antigen (22). Surveys of ETEC for the production of CFA/I, CFA/II and in some cases CFA/IV again gave varying results, from 79 % colonization factor positive in a small study in Chile [23], 75% in Bangladesh [16], 29% in Thailand [14,17] to 23% in travellers returning to Japan from South-East Asia [24].…”
Section: Introductionmentioning
confidence: 98%
“…Lanes: 1, BColV15; 2, BColV136; 3, BColV118; 4, BColV125; 5, BColV128; 6, ColV-CA7 (control); 7, DColV66; 8, DColV65; 9, DColV120; 10, DColV121; 11, DColV166; 12, DColV169. Molecular size standards: 95 megadaltons, ColV2; 56.6 megadaltons, ColVi; 65 and 42.6 megadaltons, plasmids from E. coli TR438 (5,7,13).…”
Section: Resultsmentioning
confidence: 99%